Deuteronomy Of Taghleeb In The Word Of Al-Abawani, Al-Masyriqani And Al-Bahrani In The Quran (Semantic Approach To The Quran) - Fikri, Muhammad Wildan Ali; Akbar, Ahmad Fadly Rahman; Suharto, Ahmad; Habibulloh, Ilham (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Some people only know the general form of tasniyah, even though there is another form, namely Deuteronomy of taghlib. Therefore, this research aims to discuss in detail the Deuteronomy of taghlib, especially in the three words as al-abawani, al-masyriqani, and al-bahrani. The novelty in the research is discussing the Deuteronomy of taghlib with Thosihiko Izutsu's Semantic Approach. Based on the literature reviewed, there has been limited in-depth discussion of the deuteronomy of taghlib. Therefore, this study argues that a detailed examination of the deuteronomy of taghlib in the Quran is essential. This research employed a library research. Followed by an analysis of the meanings of these three words based on Quranic semantics according to Thosihiko Izutsu, a Japanese linguist. The findings of this research indicate that the word al-abawani is the dual form of al-abu (father). In the Quran, al-abawani refers to both parents (father and mother) and is related to inheritance. In other verses, it refers to the two grandfathers of Prophet Yusuf: Prophet Ibrahim and Ishaq. In another context, al-abawani is interpreted as Adam and Eve in relation to their expulsion from Paradise. The word al-masyriqani is the dual form of masyriq, meaning "place of sunrise." In the Quran, al-masyriqani refers to the place of sunrise and sunset. In other verses, it is interpreted as the place of sunrise during summer and winter. Finally, the word al-bahrani is the dual form of al-bahru, meaning "sea." In the Quran, al-bahrani is interpreted as the meeting point of two seas.